Western Diet Induces Impairment of Liver-Brain Axis Accelerating Neuroinflammation and Amyloid Pathology in Alzheimer's Disease - Wiȩckowska-Gacek, Angelika; Mietelska-Porowska, Anna; Chutorański, Dominik; Wydrych, Małgorzata; Długosz, Jan; Wojda, Urszula (Frontiers in Aging Neuroscience, 2021)
Alzheimer’s disease (AD) is an aging-dependent, irreversible neurodegenerative disorder and the most common cause of dementia. The prevailing AD hypothesis points to the central role of altered cleavage of amyloid precursor protein (APP) and formation of toxic amyloid-β (Aβ) deposits in the brain. The lack of efficient AD treatments stems from incomplete knowledge on AD causes and environmental risk factors. The role of lifestyle factors, including diet, in neurological diseases is now beginning to attract considerable attention. One of them is western diet (WD), which can lead to many serious diseases that develop with age. The aim of the study was to investigate whether WD-derived systemic disturbances may accelerate the brain neuroinflammation and amyloidogenesis at the early stages of AD development. To verify this hypothesis, transgenic mice expressing human APP with AD-causing mutations (APPswe) were fed with WD from the 3rd month of age. These mice were compared to APPswe mice, in which short-term high-grade inflammation was induced by injection of lipopolysaccharide (LPS) and to untreated APPswe mice. All experimental subgroups of animals were subsequently analyzed at 4-, 8- and 12- months of age. APPswe mice at 4 and 8-months-old represent earlier pre-plaque stages of AD, while 12-month-old animals represent later stages of AD, with visible amyloid pathology. Already short time of WD feeding induced in 4-month-old animals such brain neuroinflammation events as enhanced astrogliosis, to a level comparable to that induced by the administration of pro-inflammatory LPS, and microglia activation in 8-month-old mice. Also, WD feeding accelerated increased Aβ production, observed already in 8-month-old animals. These brain changes corresponded to diet-induced metabolic disorders, including increased cholesterol level in 4 months of age, and advanced hypercholesterolemia and fatty liver disease in 8-month-old mice. These results indicate that the westernized pattern of nourishment is an important modifiable risk factor of AD development, and that a healthy, balanced, diet may be one of the most efficient AD prevention methods.